General nickel-catalyzed method for C-H bond alkynylation of heteroarenes through chelation assistance - Punji, Benudhar; Khake, Shrikant manmathappa; Soni, Vineeta; Gonnade, Rajesh Ghanshyam (Chemistry - A European Journal, 2017)
A general nickel-catalyzed method for the alkynylation of heteroarenes through monodentate chelation assistance is described. Many heterocycles, including indoles, pyrroles, imidazoles and pyrazole, efficiently coupled with (triisopropylsilyl)alkynyl bromide, and synthetically important functional groups, such as halides, ether, nitrile, nitro were tolerated. Synthetic applicability of this Ni-catalyzed method is demonstrated by the removal of triisopropylsilyl (-SiiPr₃) group, and further functionalization into triazolyl, benzofuranyl and alkynyl arene derivatives. Preliminary mechanistic investigations on the alkynylation of indole suggest that the reaction proceeds through kinetically relevant C-H activation and follows the two-electron redox pathway. A catalytically competent Ni-species, [(Phen)₃Ni].NiBr₄ has been isolated and structurally characterized.